Analisis Faktor Dominan Penyebab Terjadinya Pembengkakan Biaya (Cost Overrun) Pada Proyek Konstruksi Gedung Pemerintah Di Kota Pekanbaru - Saputra, Deri Afriza; Iriana, Rian Tri Komara; Sebayang, Mardani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The implementation of construction especially in Pekanbaru City, the cost factor is the first consideration because of the usually involves the amount of investment that is great for a assignor. Therefore, the cost of the project should manage by a good way that the possibility of swelling (cost overruns) can be minimized. The purpose of this research is to analyze the most dominant factors causing the swelling of costs (cost overrun) at the construction of government building projects in Pekanbaru City. The data collection was done by distributed questionnaires to small contractors in Pekanbaru area. The data collected were analyzed by using validity and reliability test, analysis factor, classical assumption test and multiple linear Regression This data processing by using computer program SPSS (Statistical Product and Service Solution) version 24. From the results of analysis obtained the most dominant factors causing the swelling of costs (cost overrun) in the government building construction project in Pekanbaru city consists of: part of planning and implementation that so many projects are handled simultaneously, the part of coordination of resources, that the shortage of labor. The portion control which is a way of payment that is not timely.Keywords: cost, cost overrun, dominant factor.